Tomorrow never dies - Spottiswoode, Roger; Feirstein, Bruce; Wilson, Michael G.; Broccoli, Barbara; United Artists Corporation; Eon Productions (Firm).; Danjaq Productions; MGM/UA Home Video (Firm).; Viva Video (Santa Monica, Calif. MGM/UA Home Video ; distributed in the Philippines by Viva Video, 2000)
Just as a media mogul unveils his new global news service, a British warship is attacked in Chinese territory. Agent James Bond teams with a beautiful Chinese spy to discover the truth before war breaks out.
Originally produced as a motion picture in 1997.
Director of photography, Robert Elswit ; editors, Dominique Fortin, Michel Arcand ; music by David Arnold.
Pierce Brosnan, Jonathan Pryce, Michelle Yeoh, Teri Hatcher, Joe Don Baker, Judi Dench.
MPAA rating: PG-13.
VCD
Keywords: Bond, James (Fictitious character) -- Drama; Intelligence officers -- Great Britain -- Drama; Women intelligence officers -- China -- Drama; Intelligence service -- Great Britain -- Drama